Emerging Efflux Pump-Mediated Cefiderocol Resistance in Pseudomonas aeruginosa Clinical Isolates from Nasiriyah, Iraq A Molecular and Phenotypic Study - Obaid, Bushra (Journal of Biomedicine and Biochemistry, 2025)
Background: The thalassemia syndromes are a group of inherent hemolyticanemias characterized by the decrease or absence of the synthesis of one or more globin chains of hemoglobin. Elevated levels of NOD-like receptor protein 3 (NLRP3) and ferritin, along with oxidative stress markers such as malondialdehyde (MDA) and catalase activity, have been linked to thalassemia disease progression and prognosis.Aim: This study aims to investigate the relationship between serum levels of NLRP3, ferritin, MDA, and catalase activity in beta-thalassemia patients compared to healthy controls, providing insights into potential diagnostic and prognostic biomarkers. Materials and Methods: (75) patients with beta-thalassemia major aged 6-18 years who were selected at the Al- Zahra Teaching Hospital/ALNAJAF AL ASHRAF CITY along with (45) normal people of the same age without any history of hematological diseases, chronic diseases, acute illness, or infection. Patients who met the selection criteria were included in the study. All subjects were enrolled in this study between November 2024 and January 2025; Serum levels of NLRP3, ferritin, MDA, and Catalase were analyzed using enzyme-linked immunosorbent assay (ELISA) and spectrophotometric methods. For data collection and statistical analysis, Microsoft Office Excel 2013 and GraphPad Prism 9.2.0 were utilized.Results: The study found elevated levels of NLRP3 in thalassemia patients (7.006 ± 1.014) compared to the healthy group (1.35 ± 0.2868), with a P value of 0.0003. Ferritin levels were also higher in patients (1576 ± 85.09 ng/ml) compared to the healthy group (73.1 ± 13.67 ng/ml), with a P value of